Implementasi Kegiatan Kolase dalam Mengembangkan Kemampuan Motorik Halus Pada Anak Usia Dini Kelompok B - Mustanirah; Muhammad Fadhil; Najmul Hayat (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
Fine Motoric is one of the delicious aspects of development in early childhood that must be developed optimally. Matter This is due because of mastery motor skills at time children will be very effect on developmentfurthermore. But in reality there are still many fine motor skills in early childhood that have not developed optimally. Therefore this study aims to find out how the development of fine motor skills in group B early childhood through activity kolase at Izzatul Islam Kindergarten, Mendalo Darat Village, Muaro Jambi Regency. The type of research being carried out is a type of qualitative descriptive analytic research in which the research results are presented in the form of words not numbers. Data collection techniques using observation, interviews and documentation. Data analysis techniques use the Miles and Huberman models. And the data validation technique uses data triangulation. The results of the study are: first, fine motor development in early childhood can develop well because it is carried out routinely, namely 2 times in 1 month, this can be seen from the children being able to perform indicators of fine motor development such as using their fingers well, being able to imitate shapes collage well, able to cut/tear well, able to spread glue on the media, able to stick collage materials on the media densely and neatly, and able to explore with various materials and media to make collages. Second, in carrying out this collage activity the teacher does it in accordance with the steps listed in the Daily Learning Implementation Plan (RPPH) and Third, namely the supporting factors in carrying out collage activities, namely the completeness of facilities and infrastructure including tools and materials, the condition of the teacher, students and imagination children, while the inhibiting factor is the child's mood.